Experimental and modelling study of energy efficiency of CO2 hydrate slurry in a coil heat exchanger. (15th May 2019) - Dufour, Thomas; Hoang, Hong Minh; Oignet, Jérémy; Osswald, Véronique; Fournaison, Laurence; Delahaye, Anthony
Highlights: Experimental and modelling study of hydrate slurry behavior in coil heat exchanger. Comparison between water and CO2 hydrate slurry with various hydrate fractions. Working time and heat exchange were improved by the presence of hydrates. Lower pressure drop than water can be obtained by reducing the slurry flowrate. Optimal fraction is found between 5 and 8 wt%. Abstract: Cold production is now facing important energy and environmental issues related to energy consumption and greenhouse gas emissions. Innovative and sustainable emerging technologies are highly needed to enhance the energy efficiency and reduce environmental impacts of refrigeration systems. Secondary loops using phase change material slurries are high-performance systems able to store and deliver high energy density fluid for refrigeration and air conditioning applications. CO2 hydrate slurries are promising due to their significant latent heat and their capacity to store and transport energy with relatively low viscosity and high heat exchange coefficients. Nevertheless, to be attractive, the thermal performance in a heat exchanger of such hydrate-based system needs to be proven. This article studies the behavior of CO2 hydrate slurry in a coil heat exchanger with both experimental and numerical approaches. The experimental approach evaluates the impact of hydrates on the heat exchanger efficiency under various operating conditions (hydrate fraction and flowrate). The results show that the use of CO2 hydrate slurries has beneficial impact on the heat exchanger efficiency and pressure drops under appropriate conditions. For example, CO2 hydrate slurry at 25 kg h −1 and 8% hydrate mass fraction presents half the pressure drop of water at 100 kg h −1, with higher heat exchange. A numerical model of the heat exchanger was also developed and validated by experimental data. Furthermore, an optimization study was proposed in order to find the hydrate fraction range that can deliver the required power (400–1100 W) without degrading the pumping power.